Appetitive behavior of the honey bee Apis mellifera in response to phenolic compounds naturally found in nectars - Gatica Hernandez, Ismaél Jairo Gabriel (2019)
The honey bee is the most frequently used species in pollination services for diverse crops. In onion crops (Allium cepa L.), however, bees avoid visiting certain varieties, being attracted differently to male sterile (MS) and fertile (OP) lines. These differences might be based on the phenolic profiles of the cultivars’ nectars. To understand the relationship between nectar composition and pollinator attraction to different onion lines, we tested sensory and cognitive abilities and palatability in honey bees exposed to MS and OP onion nectars and sugar solutions mimicking them. We evaluated the proboscis extension response (PER) after antennal contact (unconditioned response) to MS or OP onion nectars, finding no statistical differences, which denotes similar gustatory perception for both nectars. We also performed food uptake assays to test palatability of different artificial nectars, considering their flavonoids and potassium content. The presence of potassium decreased palatability of the artificial nectars. Finally, we evaluated the beeś cognitive abilities when the reward (unconditioned stimulus, US) offered during conditioning PER assays presents differences in composition. We found that potassium by itself impaired learning; however, such impairment was even higher when naringenin and quercetin were added in the US (MS mimic nectar). Interestingly, potassium together with luteolin (OP mimic nectar) improved learning. Our study demonstrates that the differences in the nectars’ flavonoid profiles combined with their high potassium content could explain the previously reported differences in attractiveness between onion lines, suggesting an important role of nectar-compounds other than sugars for the attractiveness of flowers to pollinators.